Dark sky ebook - Box, C. J. (Joe Pickett, 2021)
Don’t miss the JOE PICKETT series—now streaming on Paramount+ Wyoming game warden Joe Pickett must accompany a Silicon Valley CEO on a hunting trip—but soon learns that he himself may be the hunted—in this thrilling novel from #1 New York Times bestselling author C. J. Box.   **Winner of the Western Writers of America Spur Award for contemporary novel** When the governor of Wyoming gives Joe Pickett the thankless task of taking a tech baron on an elk hunting trip, Joe reluctantly treks into the wilderness with his high-profile charge. But as they venture into the woods, a man-hunter is hot on their heels, driven by a desire for revenge. Finding himself without a weapon, a horse, or a way to communicate, Joe must rely on his wits and his knowledge of the outdoors to protect himself and his companion. Meanwhile, Joe's closest friend, Nate Romanowski, and his own daughter Sheridan learn of the threat to Joe's life and follow him into the woods. In a stunning final showdown, the three of them come up against the worst that nature—and man—have to offer.